Experimental investigation of mechanical properties of geopolymer mortars produced with metakaolin, red mud and glass powder - Awad, Ashraf; Akcaoglu, Tulin; Cubukcuoglu, Beste; Canpolat, Orhan (Techno-Press, 2021)
Three different materials GP, RM and GGBFS in addition to MK were used to produce geopolymer mortars which were activated by using NaOH and Na2SiO3. In addition to these materials, GF was also introduced into the mixtures. The performance of the produced geopolymers was investigated by means of compressive strength, flexural strength, split tensile strength, chemical analysis and abrasion resistance measurements and microstructure investigation by means of SEM. In geopolymer mortar production MK is found more compatible with RM than GP in terms of strength development and abrasion resistance. Moreover, positive effect of GF (6 mm and 12 mm) addition was found to increase with the presence of GP and also with increased length of the fiber length.
Keywords: geopolymer; glass fiber; strength development; abrasion resistance; glass powder; red mud; metakaolin